A prospective clinical multicentre study on adult pulmonary Langerhans’ cell histiocytosis - Schönfeld, N.; Dirks, K.; Costabel, et al., U. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background: To date the clinical picture of pulmonary Langerhans’ cell histiocytosis has been described only in retrospective reports. For a better understanding, the German Scientific Study Group on the Treatment of Lung Disease (WATL) conducted an open, prospective, clinical observation study. Methods: During the period between 1994 and 2002 77 patients (40 men and 37 women) were recruited. The median observation period was 38.2 (3.2-86.7) months. Results: At the initial examination 50 patients were active smokers, 26 ex-smokers and 1 had never smoked. 36% of the patients showed reduced vital capacity, 28% signs of airways obstruction. On chest radiography, 74% of the patients who stopped smoking (24/50) showed regression, while 13% remained unchanged and 13% revealed progression. In the group that continued to smoke (25/50) chest radiography showed regression in 58% of cases, no change in 25% and progression in 17%. The difference was not significant, which was also true for lung function values. 3 patients died within the observation period. Conclusion: The data underline the key role of smoking as the sole known risk factor. A significant effect of smoking cessation on the course could not be confirmed. The overall prognosis was good in this series as compared to previous reports.